GRIT the battle within - Gupta, Ankit (New Delhi Rupa, 2022)
When life brings the battle to you, You bring the battle to life. Rise, warrior. Rise. Grit: The Battle Within is an inspirational and adventurous memoir relevant to our times. Autobiographical in nature, the book tells an incredible story of a boy whose life was turned upside down$1 (Bfrom his family falling victim to Mumbai mobsters to moving to a one-room apartment, to coming to the US with just five dollars and finally, becoming the lead engineer of the most advanced mobile chips in the world. This book takes the reader into an immigrant$1 (Bs turbulent yet triumphant journey across two countries, delving deep into the soul of a fighter and into the heart of our humanity. This story is for the dreamers and doers who want more from life and want to know how to succeed both at the personal and global level. The book, while being devastating, brave, raw and hopeful, introduces a remarkable new writer$1 (BAnkit Gupta. `s
Keywords: Memoir; Autobiography -- Literature; Non - Fiction